Application of life cycle assessment for hospital solid waste management: A case study. (2nd October 2016) - Ali, Mustafa; Wang, Wenping; Chaudhry, Nawaz
ABSTRACT: This study was meant to determine environmental aspects of hospital waste management scenarios using a life cycle analysis approach. The survey for this study was conducted at the largest hospital in a major city of Pakistan. The hospital was thoroughly analyzed from November 2014 to January 2015 to quantify its wastes by category. The functional unit of the study was selected as 1 tonne of disposable solid hospital waste. System boundaries included transportation of hospital solid waste and its treatment and disposal by landfilling, incineration, composting, and material recycling methods. These methods were evaluated based on their greenhouse gas emissions. Landfilling and incineration turned out to be the worst final disposal alternatives, whereas composting and material recovery displayed savings in emissions. An integrated system (composting, incineration, and material recycling) was found as the best solution among the evaluated scenarios. This study can be used by policymakers for the formulation of an integrated hospital waste management plan. Implications : This study deals with environmental aspects of hospital waste management scenarios. It is an increasing area of concern in many developing and resource-constrained countries of the world. The life cycle analysis (LCA) approach is a useful tool for estimation of greenhouse gas emissions from different waste management activities. There is a shortage of information in existing literature regarding LCA of hospital wastes. To the best knowledge of the authors this work is the first attempt at quantifying the environmental footprint of hospital waste in Pakistan.